The Link between Misinformation and Radicalisation: current Knowledge and Areas for Future Inquiry - Roberts-Ingleson, Elise (Perspectives on terrorism, 2023)
Does misinformation lead to radicalisation? This Research Note explores the theoretical link between consumption of misinformation and radicalisation to violent extremism. Drawing from insights from communication studies, criminology, and psychology, it is argued that some unique characteristics of misinformation are likely to facilitate radicalisation among individuals with self-uncertainty, low cognitive flexibility, and grievances, who also experience social exclusion. This exploration concludes with a summary of findings and offers recommendations for both policy makers and practitioners.